E2F1, a Novel Regulator of Metabolism - Denechaud, Pierre-Damien; Fajas, Lluis; Giralt, Albert (Frontiers in Endocrinology, 2017)
In the last years, several lines of evidence have shown that cell cycle regulatory proteins also can modulate metabolic processes. The transcription factor E2F1 is a central player involved in cell cycle progression, DNA-damage response and apoptosis. Its crucial role in the control of cell fate has been extensively studied and reviewed before, however, here we focus on the participation of E2F1 in the regulation of metabolism. We summarize recent findings about the cell cycle independent roles of E2F1 in various tissues that contribute to global metabolic homeostasis and highlight that E2F1 activity is increased during obesity. Finally, coming back to the pivotal role of E2F1 in cancer development, we discuss how E2F1 links cell cycle progression with different metabolic adaptations required for cell growth and survival.